Physiological and growth responses of lettuce plants submitted of 2,4-D simulated drift - Bianchin Rebesquini, Roberta; Teixeira Schwab, Natalia; Peligrinotti Tarouco, Camila; Rubert, Jaíne; Buffon, Paola Ana; Sielo Holkem, Aline; da Rosa Ulguim, André (Comunicata Scientiae, 2024)
Pesticide drift is due to the transport of the active ingredient to areas not targeted by spraying, causing negative effects on the sensitive crops’ development. The aim of this study was to evaluate lettuce response to simulated 2,4-D drift. Experiments were conducted in the greenhouse, in a randomized complete block design with four replications. The treatments consisted of nine different doses of the 2,4-D herbicide, which are: 0; 1.56; 3.125; 6.20; 12.5; 25; 50; 75; and 100% from the recommended dose (670 g a.a. ha-1). The application occurred when the lettuce plants had four to six true leaves. The analyzed variables were visual injury (phytotoxicity), development parameter (phyllochron), growth (rosette diameter and dry mass of the aerial part), and photosynthetic parameters (gas exchange). The lettuce crop showed high sensitivity to the 2,4-D herbicide, with the lowest dose resulting in significant phytotoxic damage to plants, and from 12.5% of the recommended 2,4-D dose, visual injuries were greater than 90%. The plants´ development and growth were negatively affected by the increased drift doses, culminating in enhanced phyllochron and reduction in rosette diameter and dry mass of the aerial part. The gas exchange of the crop was affected from 6.20% of the recommended dose, causing a reduction in the CO2 assimilation rate, stomatal conductance, transpiration rate and rubisco carboxylation efficiency.